IMPORT SUBSTITUTION AS AN INSTRUMENT OF STRATEGIC PLANNING AND FORECASTING AT INDUSTRIAL ENTERPRISES - Evgeniya Bondarenko; Evgeniya Karpunina (Вестник Северо-Кавказского федерального университета)
The article deals with import substitution as a governmental policy and as a challenging strategy of enterprise development. Purposes and specific characteristics of the three main import substitution strategies -domestic-oriented, external-oriented and mixed - are outlined. Different stages of import substitution strategy development are set forward: for industrial enterprises to be founded - at the stage of business planning, for operating industrial enterprises - at the stage of the company strategy review. The definitions of «import substitution:}, «domestic manufacturer:: and «production localization:: are specified.